2018
DOI: 10.3390/polym11010038
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Mechanism of Xylogenesis in Moso Bamboo (Phyllostachys edulis) Shoots during Cold Storage

Abstract: A bamboo shoot is the immature stem of the woody grass and a nutritious and popular vegetable in East Asia. However, it undergoes a rapid xylogenesis process right after harvest, even being stored in a cold chamber. To investigate the molecular regulation mechanisms of xylogenesis in Moso bamboo (Phyllostachys edulis) shoots (MBSes) during cold storage, the measurement of cell wall polymers (cellulose, hemicellulose, and lignin) and related enzyme activities (phenylalanine ammonia lyase (PAL), cinnamyl alcohol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…These results indicated that the winter bamboo shoots had undergone lignification during storage, in which the PeHBs might be involved in the regulating process. Moreover, the content of cellulose was increased and that of hemicellulose gradually decreased along with the storage days ( Figure S7), which was similar to the reported results [56].…”
Section: Lignification In Winter Bamboo Shoots During Storagesupporting
confidence: 90%
“…These results indicated that the winter bamboo shoots had undergone lignification during storage, in which the PeHBs might be involved in the regulating process. Moreover, the content of cellulose was increased and that of hemicellulose gradually decreased along with the storage days ( Figure S7), which was similar to the reported results [56].…”
Section: Lignification In Winter Bamboo Shoots During Storagesupporting
confidence: 90%
“…Bamboo shoots are usually harvested with a spade or hoe, which can leave a severe wound at the cut end (Kleinhenz et al, 2000). Therefore, bamboo shoots deteriorate rapidly from mechanical injury during harvest, resulting in significant loss of quality (Li et al, 2019a). The degradation of nutrients and interstitial and woody fibers leads to physical and chemical changes in fresh bamboo shoots, which, in turn, negatively limit the shelf life during storage and affect consumer preferences (Pongprasert et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Large-scale plantings of bamboo usually takes no more than six years to reach harvestable size in China. The study of the lignification of bamboo has mostly focused on the growth pattern and anatomical structure of bamboo [17]. However, the chemical quantification of lignin has not been explored at different bamboo ages.…”
Section: Introductionmentioning
confidence: 99%
“…The purpose of this paper is to investigate the changes in chemical structure and content of lignin of bamboo with ages (1-6 years old). Based on the previous research [17,18], the analysis of bamboo lignin in different years was carried out by Nuclear Magnetic Resonance (NMR), Fourier Transform infrared spectroscopy (FT-IR), Gel Permeation Chromatography (GPC), and changes in lignin chemical structures during the whole lignification process was observed visually.…”
Section: Introductionmentioning
confidence: 99%